Regulation of MAP2, GFAP, and calcium in the CA3 Region Following Kainic Acid Exposure to organotypic hippocampal slice culture [version 3; peer review: 2 approved] - Aulanni'am Aulanni'am; Kusworini Handono; Ettie Rukmigarsari; Hidayat Sujuti; Machlusil Husna (F1000Research)
Background Neurodegeneration due to neurotoxicity is one of the phenomena in temporal lobe epilepsy. Experimentally, hippocampal excitotoxicity process can occur due to kainic acid exposure, especially in the CA3 area. Neuronal death, astrocyte reactivity and increased calcium also occur in hippocampal excitotoxicity, but few studies have investigated immediate effect after kainic acid exposure. The organotypic hippocampal slice culture (OHSC) is a useful model for studying the neurodegeneration process, but there are still many protocol differences. In this study, minor modifications were made in the OHSC protocol. Methods OHSC was obtained from three healthy wild type Wistar rats aged P10. Healthy culture slices were obtained and lasted up to 10 days in vitro (DIV 10). Bath application of kainic acid for 48 hours in DIV 10 followed by observation of its initial effects on neurons, astrocytes, and calcium via the expression of MAP2, GFAP, and intracellular calcium imaging, subsequently. Results After 48 h of kainic acid administration, there was a significant increase in intracellular calcium intensity (p = 0.006 < α), accompanied by a significant decrease in MAP2 (p = 0.003 < α) and GFAP (p = 0.010 < α) expression. Conclusion These findings suggest early neuronal and astrocyte damage at the initial onset of hippocampal injury. This implies that astrocyte damage occurs early before an increase in GFAP that characterizes reactive astrogliosis found in other studies. Damage to neurons and astrocytes may be associated with increased intracellular calcium. It is necessary to develop further research regarding regulation of calcium, MAP2, and GFAP at a spatial time after exposure to kainic acid and strategies to reduce damage caused by excitotoxicity.